The policing mind : developing trauma resilience for a new era - Miller, Jessica K. (Policy Press, 2022)
How does it feel to be a police officer? Jessica Miller uses the most recent neuroscience and real-life examples to explore risks to individual resilience. A compulsory read for anyone with an interest in policing, the book offers practical resilience techniques and policy recommendations for police officers facing crime in a post-COVID world.
Keywords: Police psychology.; Resilience (Personality trait); Psychologie policière.; Résilience (Trait de personnalité); SOCIAL SCIENCE / Criminology.; Police psychology